PROCESS OF THE WITCH’S DIALOGUES IN SNOW WHITE AND THE HUNTSMAN MOVIE - Siti Arfah; Rahmah Rahmah (LINGUISTICA, 2013)
ABSTRACT   This  study  is  concerned with Transitivity  System,  focusing on the  Process  in Snow White and the Huntsman Movie (the main character of the movie: Ravenna). This study was conducted by  using descriptive  qualitative  design.  There  are  six  types  of  process  in 145 clauses.  The  result  of  data  analysis  showed that  the  numbers  in types  of  process  were: Material  Process  (56.55%),  Mental  Process  (13.1%),  Relational  Process  (24.8%),  Verbal Process  (3.45%),  and Existential  Process  (2.1%).  It  means  that  Material    process  is  the dominant  type of process used in Ravenna’s utterances (55.56%). The reason why material process was the most dominant was Ravenna displayed action scenes in the movie. Then the material process influences her act became action scene.Keywords: Functional Grammar, Transitivity, Process.